2018
DOI: 10.1002/hec.3776
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation of the health economic impacts of bariatric surgery for obesity and implications for improved practice in health economics

Abstract: Obesity is an economic problem. Bariatric surgery is cost-effective for severe and resistant obesity. Most economic evaluations of bariatric surgery use administrative data and narrowly defined direct medical costs in their quantitative analyses. Demand far outstrips supply for bariatric surgery. Further allocation of health care resources to bariatric surgery (particularly public) could be stimulated by new health economic evidence that supports the provision of bariatric surgery. We postulated that qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Importantly, 45.8% of these potential bariatric surgery candidates had no private health insurance [24]. Our recent qualitative health economics study found that many of the people who partially or fully self-funded their bariatric surgery experienced economic burden to do so [25]. This qualitative study also found that some people were accessing their superannuation to fund their surgery because they either had no private health insurance or they had to pay the concomitant health insurance gap [25].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, 45.8% of these potential bariatric surgery candidates had no private health insurance [24]. Our recent qualitative health economics study found that many of the people who partially or fully self-funded their bariatric surgery experienced economic burden to do so [25]. This qualitative study also found that some people were accessing their superannuation to fund their surgery because they either had no private health insurance or they had to pay the concomitant health insurance gap [25].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of method, recent studies within health economics have also found value in using a deliberative approach to enable reflection and collect both qualitative and quantitative data simultaneously (Gansen, Klinger, & Rogowski, 2019; Kinghorn, 2019). There have also been attempts to use qualitative methods to enhance understanding of the values of relevant stakeholders that can be incorporated into decision‐making around health and care services (Campbell et al., 2018; Kinghorn & Coast, 2019). The extent of this work remains limited, however, and methodological issues such as the extent of deliberation that is optimal in these contexts have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge in estimating health-services utilization with administrative data is that often, services covered by major insurance companies are more likely to be recorded, while many out-of-pocket expenses are not captured 57 . Also, certain diagnoses are less likely to be coded.…”
Section: Uses and Misuses Of Large Databases For Cost-effectiveness R...mentioning
confidence: 99%